The Influence of Customer Experience, Trust, and Word of Mouth on Service Use Decisions at Zap Clinic in Mataram City - Mahadewi, Komang Ganitri; HS, Rusminah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to find out and analyze the influence of customer experience, trust, and word of mouth on the decision to use services at ZAP Clinic Mataram City. The type of research used is quantitative with an associative approach. The population in this study is all consumers who have used beauty Zap Clinic services in Mataram City. The number of samples taken was 100 people. The sample collection technique used is non-probability sampling with a purposive sampling approach. The results of the study showed that customer experience and trust had a positive and significant effect on service usage decisions, while word of mouth had a positive but not significant effect. The ability or contribution of the variables of customer experience, trust, and word of mouth in shaping usage decisions was 77.9%, while the remaining 22.1% was influenced by other factors that were not included in the model. These findings emphasize the importance of consumer experience and trust, so ZAP Clinic is advised to improve digital interaction and customer loyalty programs.